2020
DOI: 10.1261/rna.074302.119
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical influences on nonenzymatic oligomerization of prebiotically relevant cyclic nucleotides

Abstract: The spontaneous emergence of long RNA molecules on the early Earth, a phenomenon central to the RNA World hypothesis, continues to remain an enigma in the field of origins of life. Few studies have looked at the nonenzymatic oligomerization of cyclic mononucleotides under neutral to alkaline conditions, albeit in fully dehydrated state. In this study, we systematically investigated the oligomerization of cyclic nucleotides under prebiotically relevant conditions, wherein starting reactants were subjected to re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…Therefore, in future studies, it would be important to look at changes in membrane lamellarity as a function of wet‐dry cycles. Previous studies have demonstrated that multiple wet‐dry cycles result in the oligomerization of monomers such as nucleotides and amino acids [10–18] . When vesicles reform, the oligomers can get encapsulated within these vesicles forming protocellular entities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in future studies, it would be important to look at changes in membrane lamellarity as a function of wet‐dry cycles. Previous studies have demonstrated that multiple wet‐dry cycles result in the oligomerization of monomers such as nucleotides and amino acids [10–18] . When vesicles reform, the oligomers can get encapsulated within these vesicles forming protocellular entities.…”
Section: Discussionmentioning
confidence: 99%
“…Fluctuating environments on the prebiotic Earth, driven by thermal evaporation, geyser activity, rainfall etc., give rise to wet‐dry cycles [8,9] . Such naturally recurring wet‐dry cycles have been demonstrated to promote formation of different building blocks of life, e. g., oligoesters, [10,11] oligopeptides, [12,13] nucleotides [14,15] and oligonucleotides [16–18] etc. High temperature in these niches induces water loss, which tends to concentrate dilute solutions and promote thermodynamically uphill condensation reactions [8,9] .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above observations, we set out to investigate the ability of metal ions to coordinate with TPPS and discern if metal‐coordinated TPPS (M‐TPPS) complexes could result under prebiotically plausible terrestrial geothermal conditions. In addition to being widely considered as a niche pertinent to discerning the emergence of life on the early Earth, these prebiotic settings have previously been shown to facilitate the formation of biopolymers relevant to extant biochemistry [50–54] . Towards this, aqueous solution containing 0.3 mM metal ions and 0.03 mM (ten times lower than metal ion) TPPS was incubated at 70° C, simulating putative early Earth conditions [55] (details in Experimental Section).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to being widely considered as a niche pertinent to discerning the emergence of life on the early Earth, these prebiotic settings have previously been shown to facilitate the formation of biopolymers relevant to extant biochemistry. [50][51][52][53][54] Towards this, aqueous solution containing 0.3 mM metal ions and 0.03 mM (ten times lower than metal ion) TPPS was incubated at 70°C, simulating putative early Earth conditions [55] (details in Experimental Section). Metal coordination with the TPPS scaffold was monitored at specific time points using the temporal change observed in the UV absorption spectrum and steady-state fluorescence spectroscopy (Supporting Information Figures S11-22).…”
Section: Chembiochemmentioning
confidence: 99%
“…Our observations of cAMP and cUMP forming up to trimers are consistent with literature. [27,28] The polymerisation is demonstrated in the presence of bulk water at the air-water interface, within a microfluidic thermal chamber. The chamber mimics conditions of a heated, water filled volcanic rock pore that includes a gas bubble.…”
Section: Introductionmentioning
confidence: 99%